A variação entre formas de futuro do pretérito e de pretérito imperfeito no português informal no Rio de Janeiro - Costa, Ana Lúcia dos Prazeres (1997)
This dissertation deals with the variation among tenses of the conditional and the past-imperfect indicative - considering both their inflected and periphrastic forms with the auxiliary verb 'ir' ['to go'] - in the expression of the irrealis mode, in the informal Portuguese which is spoken (sociolinguistic interviews) and written (personal letters) in Rio de Janeiro. First of all, we delineate a definition for the notion which the variants have in commom: the irrealis. We adopt the theoretical and methodological principles of the Theory of Linguistic Variation and Change, associated with hypotheses based on the Functional Linguistics. We review texts which treat this phenomenum according to either a grammatical or a linguistic approach. Then, the samples of spoken and written language used in this research are described. We work with the conventional social factors and with linguistic factors of a sintactic, semantic or discoursive nature. Finally, we evaluate the peculiarity of this phenomenum of variation in what concerns modal verbs.